GREEN DIPLOMACY" AS A MEANS OF IMPLEMENTING INTERNATIONAL LEGAL POLICY IN THE ENVIRONMENTAL SPHERE IN THE CONTEXT OF GLOBALIZATION - V. Khizhnyak (Гуманитарные и юридические исследования)
Globalization processes are an objective phenomenon of the modern world. Starting with economic relations, globalization processes have embraced other areas of public life, including relations to protect the environment. In order to minimize their risks in these conditions, states must competently build their international legal policy in international relations. Therefore, it is necessary to search for new approaches to the participation of states in such relations and new means of implementing their international legal policy. Thus, the processes of globalization in international relations cause the emergence of new phenomena, which include environmental or "green diplomacy". The urgency of considering the problems of implementing "green diplomacy" stems from the fact that at present, it is beginning to be increasingly used by states as a means of implementing their international legal policies in the environmental sphere. At the same time, in the legal literature there is no consensus on the content of this concept and its essence. In addition, there is no consensus on the term itself. The term "green diplomacy" is most commonly used, less commonly, "environmental diplomacy". The novelty of this work is that it analyzes the essence of this phenomenon, its features in the international legal policy of various states, the relationship with other related concepts. To study these aspects of the implementation of "green diplomacy" the comparative legal method, methods of analysis and synthesis were used. Because of the study, such concepts as international legal policy in the environmental sphere, environmental or "green diplomacy" were formulated. The content, fundamentals and practice of implementing "green diplomacy" by states of different regions are analyzed. The author identiies the subjects involved in the implementation of "green diplomacy" and substantiates its relationship with international legal policy and the processes of globalization and global regionalization.